Comparative Advantage, Exchange Rates, and G-7 Sectoral Trade Balances - Golub, Stephen (IMF Working Papers; Working Paper ;, 1994)
This paper uses a Ricardian framework to clarify the role of microeconomic and macroeconomic factors governing the time series and cross-section behavior of sectoral trade balances. Unit labor costs and trade balances are calculated for several sectors for the seven major industrial countries. The time series and cross-section variation in sectoral unit labor costs is decomposed into relative productivity, wage differentials, and exchange rate variations. The main findings are that changes over time in sectoral trade balances, especially for the United States and Japan, are quite well explained by the evolution of unit labor cost, suggesting that trade patterns conform to comparative advantage. The cross-section results are, however, less conclusive.